Penjadwalan Mata Pelajaran Menggunakan Integer Nonlinear Programming - Mile, Abdul Rasyid; Katili, Muhammad Rifai; Nurwan, Nurwan (Research in the Mathematical and Natural Sciences, 2022)
Timetabling is one of the problems faced by large numbers of institutions, including schools. In this paper, this timetabling problem is mathematically modeled using Integer Nonlinear Programming to optimize the result with the non-linear objective function or constraint function. The model was implemented to solve the timetabling problem in one of Madrasah Tsanawiyah Islamic junior high school in Gorontalo. The result effective solutions in the form of subject and instructor timetabling that overcome the obstacles are obtained. To better the timetabling, supplementary teachers are still required for some subjects.